Outcome-Oriented and Dual-Wheel-Driven: Reforming Food Nutrition Education through “Project + Competition” under the OBE Concept - Li, Ning; Peng, Yan; Song, Lianjun; Gao, Xiaoping; Li, Qian; Zhao, Peijun; Huang, Xianqing; Li, Tiange (Journal of Research in Vocational Education, 2026)
Current pedagogical practices in food nutrition education often suffer from a disconnect between theoretical knowledge delivery and practical skill development, low student engagement, and rigid assessment methods. To address these challenges, this study proposes a blended teaching reform model guided by the Outcome-Based Education (OBE) framework, integrating a “project-driven” and “competition-empowered” dual approach. The model incorporates practical task modules-such as nutrition consultation and recipe development-within a “online self-directed learning + offline collaborative inquiry” instructional pathway. Furthermore, it systematically integrates academic competitions, including the National Undergraduate Life Sciences Competition, into the curriculum to establish a closed-loop teaching system characterized by “project-guided learning, competition-enhanced learning, and outcome-verified learning.” This paper elaborates on the structural framework and implementation strategies of the model, covering the redefinition of course objectives, restructuring of content, blended teaching design, and dynamic assessment mechanisms. The proposed approach offers a student-centered, competency-oriented, and practically actionable reform perspective for food nutrition and related applied disciplines, with potential implications for enhancing educational outcomes and learner readiness in professional settings.